Psicoterapia en adolescentes con estructura labil - Speier, Anny (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A certain group of adolescents show, apart from the peculiar lability of adolescence, a pathological personality structure, including weakness of the ego and a tendency toward disintegration. This group has received various designations, such as “borderline,” “ labile ego structure,” “latent schizophrenia.”